Enhancing the College Student Experience: Outcomes of a Leisure Education Program. (March 2018) - Jordan, Katherine A.; Gagnon, Ryan J.; Anderson, Denise M.; Pilcher, June J.
Background: Experiential education in higher education provides opportunities for college student development that contribute to student success. As such, a leisure education program is posited as a complement to experiential education programming.Purpose: This study explored the impact of a leisure education program (leisure skills) on dimensions of college student success, including school satisfaction, student life satisfaction, school belonging, and self-esteem.Methodology/Approach: This study compared 531 leisure skills students with a group of 136 students not enrolled in a leisure skills class.Findings/Conclusions: The results of a repeated-measures analysis indicated leisure skills students fared better than non–leisure skills students in the measured dimensions, maintaining similar levels of school satisfaction, life satisfaction, belonging, and self-esteem over the course of the semester while the non–leisure skills students experienced decreases.Implications: Students who chose leisure skills classes experienced stability and improvement in school and student life satisfaction, school belonging, and self-esteem. Therefore, leisure education programming should be further examined as a mechanism for college student success.